Antiviral activities of mycophenolic acid and IMD‐0354 against SARS‐CoV‐2. (25th July 2020) - Kato, Fumihiro; Matsuyama, Shutoku; Kawase, Miyuki; Hishiki, Takayuki; Katoh, Hiroshi; Takeda, Makoto
Abstract: In this study, the anti–severe acute respiratory syndrome coronavirus‐2 (anti‐SARS‐CoV‐2) activity of mycophenolic acid (MPA) and IMD‐0354 was analyzed. These compounds were chosen based on their antiviral activities against other coronaviruses. Because they also inhibit dengue virus (DENV) infection, other anti‐DENV compounds/drugs were also assessed. On SARS‐CoV‐2‐infected VeroE6/TMPRSS2 monolayers, both MPA and IMD‐0354, but not other anti‐DENV compounds/drugs, showed significant anti‐SARS‐CoV‐2 activity. Although MPA reduced the viral RNA level by only approximately 100‐fold, its half maximal effective concentration was as low as 0.87 µ m, which is easily achievable at therapeutic doses of mycophenolate mofetil. MPA targets the coronaviral papain‐like protease and an in‐depth study on its mechanism of action would be useful in the development of novel anti‐SARS‐CoV‐2 drugs.